Diversification strategies and their impact on farm performance - Salvioni, Cristina; Fontanella, Lara (Applied Studies in Agribusiness and Commerce, 2013)
The objective of this study is to identify factors determining the economic performance of agricultural holdings in Italy, with specific attention to the impact of the adoption of on-farm diversification strategies, namely income diversification and product differentiation. The adoption of these kinds of strategies has been increasingly recognised as a viable business option in agriculture as they allow better allocation of farm resources and an increase in the quota of value added retained on farms and therefore not passed on to other agents operating at the end of the food supply chain. By using a panel of professional Italian farms over the time period of 2003-2009, we estimate random effect, ordinary least square and quantile regression models to estimate the impact of income diversification and product differentiation strategies on the levels of farm income per unit of labour income. Our findings show that scale economies are important positive determinants of farm economic performance. On the contrary, when the family play an important role in the farm business, economic performance is worse. Finally, we do not find evidence of a statistically significant impact of the adoption of income diversification and product differentiation strategies. This latter result may be interpreted as a signal that farms use these strategies as risk management tools rather than as income increasing ones.